On the equicontinuity of families of mappings in the case of variable domains - Sevost'yanov, E. A.; Skvortsov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.5 We study the problem of local behavior of maps in the closure of a domain in the Euclidean space. The equicontinuity of families of these mappings is established in the case where the mapped domain is not fixed. We separately consider the domains with bad and good boundaries, as well as the homeomorphisms and maps with branching.